Desvendando o modo de ação (MOA) cancerígeno do diuron [3-(3,4-Diclofenil)-1,1-Dimetiluréia] no urotélio de ratos - Rocha, Mitscheli Sanches da [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Diuron, a substituted urea herbicide, was carcinogenic to the urinary bladder of Wistar rats at high dietary levels (2500 ppm), with a higher incidence in males. Its proposed carcinogenic mode of action (MOA) includes urothelial cytotoxicity and necrosis followed by sustained regenerative cell proliferation and urothelial hyperplasia. Urothelial cytotoxicity could be induced either by urinary solids or by chemical toxicity by diuron and/or metabolites excreted in the urine. To further elucidate the diuron urothelial MOA in male Wistar rats, this study aimed to: 1) evaluate the possible influence of urinary solids on the development of urothelial lesions; 2) determine the time course and sequence of bladder cytotoxic and proliferative changes; and 3) evaluate the toxicity of the main diuron metabolites on the urothelium. Rats treated with diuron and with NH4Cl for urinary acidification showed decreased urinary pH and reduced amounts of urinary crystals and precipitates. No difference in the incidence of urothelial lesions was found between diuron and diuron+NH4Cl treated groups indicating that cytotoxicity is not due to urinary solids. Rats treated with diuron during 1, 3 and 7 days showed urothelial cell swelling beginning on day 1. Swollen cells at day 7 presented degenerative changes such as distention of the cytoplasm, organelles and nuclei characteristic of cytolysis. By day 28, bladder urothelium in the diuron-treated group showed extensive necrosis, exfoliation and piling up of cells suggestive of hyperplasia. At 8 weeks, the bladder urothelium showed necrosis, exfoliation and significantly increased incidence of simple hyperplasia. The metabolite DCPU was found in rat urine at concentrations above the in vitro IC50 evaluated in a rat urothelial (MYP3) cell line. Moreover, DCPU induced more alterations of gene expression than the other metabolites in rat urothelial cells. Taken together, these results suggest the urothelial carcinogenic MOA of diuron is metabolism to cytotoxic metabolites, producing urothelial cell degeneration, necrosis and exfoliation, followed by sustained regenerative cell proliferation, leading to hyperplasia and eventually tumors after continued diuron exposure.

Diuron, um herbicida derivado da uréia, foi cancerígeno para a bexiga urinária de ratos Wistar quando administrado via dieta em altas concentrações (2500 ppm), com maior incidência dessa neoplasia em ratos machos. O modo de ação (MOA) cancerígeno proposto envolve citotoxicidade urotelial e necrose, seguido por proliferação celular regenerativa e hiperplasia. Citotoxicidade urotelial pode ser induzida tanto pela presença de sólidos na urina, quanto por toxicidade exercida pelo diuron e/ou seus metabólitos. Para melhor esclarecer o MOA do diuron em ratos Wistar machos, o presente estudo teve como objetivo: 1) Avaliar os efeitos dos sólidos urinários no desenvolvimento das lesões uroteliais; 2) Determinar a temporalidade e sequência das lesões citotóxicidade e proliferativas; 3) Avaliar a citotoxicidade dos principais metabólitos do diuron no urotélio. Ratos tratados com NH4Cl para acidificação da urina mostraram diminuição do pH e redução na quantidade de cristais e precipitados urinários. Não houve diferença na incidência de lesões uroteliais entre ratos tratados com diuron e ratos tratados com diuron+ NH4Cl, indicando que a citotoxicidade não ocorre devido a presença de sólidos na urina. Ratos tratados com diuron durante 1, 3 e 7 dias mostraram edema celular sob microscopia de varredura, iniciado logo após o primeiro dia de tratamento. Sob microscopia eletrônica de transmissão, no dia 7 as células uroteliais mostraram degeneração vacuolar e distensão do citoplasma, organelas e núcleo, características de citólise. No dia 28, as bexigas do grupo tratado com diuron mostraram extensas áreas de necrose, exfoliação e empilhamento celular sugestivo de hiperplasia. Após 8 semanas de tratamento, as bexigas mostraram necrose, exfoliação e aumento significativo na incidência de hiperplasias. O metabólito DCPU foi encontrado na urina de ratos tratados em concentrações maiores do que a IC50 verificada in vitro com células uroteliais (MYP3) de rato. Além disso, DCPU induziu maiores alterações na expressão gênica de células uroteliais do que os outros metabólitos testados. Nossos resultados sugerem que MOA cancerígeno do diuron ocorre por meio de citotoxidade causada por seus metabólitos, principalmente DCPU, resultando em degeneração, necrose e exfoliação celular, seguido de proliferação celular regenerativa, levando a hiperplasia e eventualmente a tumores após exposição contínua a esse herbicida
Elucidating the carcinogenic mode of action of diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] on the rat urothelium
Keywords: Diuron; Modo de ação; Urotélio; Citotoxicidade